Toward Good Simulation Practice Best Practices for the Use of Computational Modelling and Simulation in the Regulatory Process of Biomedical Products - Viceconti, Marco; Emili, Luca.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book, the Community of Practice led by the VPH Institute, the Avicenna Alliance, and the In Silico World consortium has brought together 138 experts in In Silico Trials working in academia, the medical industry, regulatory bodies, hospitals, and consulting firms. Through a consensus process, these experts produced the first attempt to define some Good Simulation Practices on how to develop, evaluate, and use In Silico Trials. Good Simulation Practice constitutes an indispensable guide for anyone who is planning to engage at any title with In Silico Trials. This book is open access, which means that you have free and unlimited access. Offers readers a unique guide to In Silico Trials Documents consensus process run by the most authoritative organizations worldwide in the field Represents the first attempt to produce a consensus position on the best practice for In Silico Trials.
Introduction -- Theoretical foundations of Good Simulation Practice -- Model development -- Model credibility -- Possible regulatory pathways -- Possible Health Technology Assessment pathways -- Ethical review of in silico methodologies -- The sponsor -- The investigator: modellers and analysts.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Biomedical engineering; Bioethics; Computer simulation; Biomedical Engineering and Bioengineering; Bioethics; Computer Modelling